Factors Associated with Minimum Dietary Diversity among Breas tfed Children Aged 6-23 Months in Indonesia (Analysis of Indonesia DHS 2017) - Aniza Rizky Aprilya Sirait; Endang L Achadi (Indonesian Journal of Public Health Nutrition, 2020)
AbstractPoor comp lementary feeding practices can lead to malnutrition in infants and young children . Minimum dietary diversity (MDD) is one of the determinants of children’s nutritional status and has been found to predict stunting. This study examined factors associated with MDD achievement among breastfed children aged 6-23 months based on Indonesia’s Demographic and Health Survey 2017. This study us ed chi-square and multiple logistic regression to analyze the data. Among 2,976 children only around 53% children met MDD recommendation. Multivariate analysis found that the diversity of diet is better among older children than younger children. Children aged 18-23 months have possibility of 5.7 times higher to achieve MDD than children aged 6-11 months and 1.3 times higher than children aged 12-17 months . Children of wealthier family (3 rd quintile and above), those delivered by trained healt h personnel, children of higher mothers’ education, working mothers, fathers’ involve in child care , ANC visit >= 4 times, and parents reside in u rban areas have possibility of having higher MDD achievement significantly than the other groups . The low MDD achievement among children aged 6-11 months warrant the importance of prioritizing effort on this age group because this is a period where a child grows rapidly and potentially expose to infection as a result of un -hygienic food preparation , and will affect the child’s growth later on .AbstrakPraktik MP-ASI yang buruk dapat menyebabkan kekurangan gizi pada anak -anak.a Ragam Asupan Minimal ( MDD) merupakan salah satu penentu status gizi anak dan dapat memprediksi terjadinya stunting . Penelitian ini membahas mengenai faktor -faktor yang berhubungan dengan capaian MDD pada anak yang diberi ASI usia 6 -23 bulan berdasarkan data SDKI tahun 2017 . Penelitian ini menggunakan uji Chi -square dan uji regresi logistik ganda untuk menganalisis data. Dari 2 ,976 anak usia 6 -23 bulan yang diberi ASI di Indonesia tahun 201 7, h anya sekitar 5 3 % anak yang telah mencapai MDD. Hasil analisis multivariat menunjukkan ba hwa capaian MDD lebih baik pada anak yang berusia lebih tua. Anak umur 18 -23 bulan mempunyai kemungkinan sebesar 5.7 kalinya untuk mencapai MDD dan anak umur 12 -17 bulan sebesar 1.3 kalinya, dibandingkan dengan bayi umur 6 -11 bulan. Anak yan g berasal da ri keluarga lebih mampu (kuintil 3 atau lebih), yg lahir ditolong tenaga kesehatan terlatih, anak dari ibu yang berpendidikan lebih tinggi, ibu yang bekerja, ayah yang berperan dalam mengurus anak, ibu yang melakukan kunjungan ANC > 4 kali dan orang tua t inggal di perkotaan, mempunyai kemungk inan lebih besar secara bermakna untuk mencapai MDD sesuai anjuran . Rendanhya capaian MDD pada bayi 6 -11 bulan menunjukkan pentingnya memberikan perhatian pada kelopmpok ini karena merupakan kelompok yang masih tumbuh dengan cepat dan mulai terpapar dengan kemungkinan terjadiya infeksi akibat penyiapan makanan yang tidak hygienis, dan akan berpengaruh terhadap pertumbuhan selanjutnya .